Aplikasi Media Pembelajaran Teknologi Augmented Reality Berbasis Android - Rizky Sahril Djaina; Syahrial Syahrial; Mohamad Ilyas Abas (Universitas Muhammadiyah Gorontalo, 2021)
This research was conducted at SMK N 3 Gorontalo, which aims to develop learning media applications using augmented reality technology. At first the teaching system only led to conventional teaching, namely through power point teaching materials and print media as well as the lack of available hardware or network equipment and the absence of computers that were ready to be disassembled and then developed using augmented reality technology. Through this research, it is hoped that the learning process will be more interactive. This application was developed using a prototype system development method that has a Requirements Gathering and Analysis phase, Quick Design, Build Prototype, User Evaluation, Refining Prototype and Engineer Product. The result of this study is a software application, namely an android-based augmented reality technology learning media application.